Electrophysiological and Morphological Properties of Neurons in Layer 5 of the Rat Postrhinal Cortex - Sills, Joeseph B. (2012)
The postrhinal cortex (POR) of the rat is homologous to the parahippocampal cortex of the primate based on connections and other criteria. Postrhinal cortex provides the major visual and visuospatial input to the hippocampal formation, both directly to CA1 and indirectly through connections with the medial entorhinal cortex. Although the cortical and hippocampal connections of the postrhinal cortex are well described, the physiology of postrhinal neurons has not been studied. Here we examined the electrical and morphological characteristics of layer 5 neurons from postrhinal cortex of 14-16 day-old rats using an in vitro slice preparation. Neurons were subjectively classified as regular-spiking (RS), fast-spiking (FS) or low threshold-spiking (LTS) based on their electrophysiological properties and similarities with neurons in other regions of neocortex. Cells stained with biocytin included pyramidal cells and interneurons with bitufted or multipolar dendritic patterns. Similarity analysis using only physiological data yielded three clusters that corresponded to FS, LTS, and RS classes. The cluster corresponding to the FS class was composed entirely of multipolar nonpyramidal cells, and the cluster corresponding to the RS class was composed entirely of pyramidal cells. The third cluster, corresponding to the LTS class, was heterogeneous and included both multipolar and bitufted dendritic arbors as well as one pyramidal cell. We did not observe any intrinsically bursting pyramidal cells, which is similar to entorhinal cortex but unlike perirhinal cortex. We conclude that POR includes at least two major classes of neocortical inhibitory interneurons, but has a functionally restricted cohort of pyramidal cells.